MEMBANGUN NILAI-NILAI MODERASI BERAGAMA DI TENGAH MASYARAKAT PLURAL: SEBUAH PENDEKATAN FILSAFAT AGAMA - Siswadi, Gede Agus; Candrawan, Ida Bagus Gede; Puspadewi, I Dewa Ayu (Lembaga Penerbit Sekolah Tinggi Hindu Dharma Klaten, 2024)
This research aims to examine and develop the values of religious moderation in a plural society through a philosophy of religion approach. Religious moderation is a very important attitude in maintaining harmony and social stability in a diverse society. This is because when religion is only interpreted as a doctrine, it will lead to excessive religious fanaticism. Therefore, believing in religious teachings must be understood with rationality, so that the principles that exist in every religious teaching can provide peace and harmony between human beings. This research uses a qualitative method with a philosophical descriptive approach. The results of this study show that religion actually provides guidance for people in thinking, acting or speaking well, by prioritising ethics and morals and humanitarian principles. However, if religious teachings are understood only as doctrine, it will be vulnerable to religious fanaticism, therefore religion should be understood rationally. Therefore, religious moderation by promoting the values of tolerance, harmony, and peace should be based on rational, critical principles in understanding religious teachings, so it is important to understand the philosophy of religion as a foundation in building religious moderation values.